2023
DOI: 10.3390/ijerph20065010
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability and Agency in the Time of COVID-19: The Narratives of Child and Youth Care Workers in South Africa

Abstract: In this paper, we use data generated through one-on-one interviews with 12 purposively sampled Child and Youth Care Workers to examine their narratives of work and life-related vulnerabilities and agency during the peak of the COVID-19 global pandemic in KwaZulu-Natal, South Africa. Our findings show that Child and Youth Care Workers were vulnerable to poor mental health. Indeed, working and socialising during the height of COVID-19 posed a mental toll on the Child and Youth Care Workers in this study, who exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…Furthermore, Masuku et al [17] specified that child and youth caregivers were exposed to poor mental health because they experienced anxiety, insecurity, and stress. Moreover, these workers have faced challenges when working under the socalled new normal, which was introduced as part of a non-pharmaceutical response to contain the spread of COVID-19 [17].…”
Section: Challenges In Coping With Covidmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Masuku et al [17] specified that child and youth caregivers were exposed to poor mental health because they experienced anxiety, insecurity, and stress. Moreover, these workers have faced challenges when working under the socalled new normal, which was introduced as part of a non-pharmaceutical response to contain the spread of COVID-19 [17].…”
Section: Challenges In Coping With Covidmentioning
confidence: 99%
“…Furthermore, Masuku et al [17] specified that child and youth caregivers were exposed to poor mental health because they experienced anxiety, insecurity, and stress. Moreover, these workers have faced challenges when working under the socalled new normal, which was introduced as part of a non-pharmaceutical response to contain the spread of COVID-19 [17]. According to Banda Chitsamatanga and Malinga [18], the hasty spread of COVID-19 leads to panic around the world and calls into question the preparedness of public health systems to deal with it.…”
Section: Challenges In Coping With Covidmentioning
confidence: 99%
“…The COVID-19 pandemic has presented many challenges to children orphaned by the virus, leaving them in a vulnerable state both emotionally and psychologically. 11 During this challenging time, music therapy can provide a safe and supportive environment for these children to process their emotions and deal with the grief of losing a parent. 12 Research has shown that music therapy can effectively reduce anxiety and stress, improve mood regulation, and increase overall well-being.…”
mentioning
confidence: 99%